FORM OF SEISMIC HORIZON ON TIME SECTION AND REFLECTED WAVE COMMON SHOT POINT TRAVEL TIME CURVE IN TRANSITION ZONE FOR THE CASE OF COMPLICATION OF TARGET HORIZON COVER BY FAULT - Ahmadov, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper is devoted to study of reflection pattern (seismic horizon) and CSP travel time curve of reflected wave when the base of seismic oscillations receivers is within transition zone, i.e. the portion of base is in one flank while the other part is already in the next flank. The equation has been derived for travel time curve of zero-offset survey, i.e. reflection pattern) for the case when target horizon cover is complicated by fault. The other equation derived is the equation of traveltime curve of CSP of reflected wave, which upgoing rays are refracted on the fault line. For this, we have used the equation of traveltime curve of normal reflections refracted on the fault line. Based on derived formulae we have calculated traveltime curves of CSP for various models of environment. Analysis of these models has shown that while passing through seismic waves receiver base over the faulted zone the travel time curve is divided into two cuts with differing curvature and various time offsets relative to each other depending on velocity section difference from the fault line leading to the impression that these two cuts are not the sections of the same travel time curve.